Autonomous topology optimisation for unstructured Peer-To-Peer networks. (26th May 2009) - Wan, Haoyi; Ishikawa, Norihiro; Hjelm, Johan
The topology of a Peer-To-Peer (P2P) overlay network is usually constructed randomly without considering the characteristics of underlying physical links. Thus, searching and routing between peer nodes is often inefficient. This paper proposes a mechanism that a peer node autonomously optimises the topology of a P2P network based on the metrics of underlying networks. The simulation results show that this mechanism optimises the topology of a P2P network and significantly decreases the average hop count between any pair of peer nodes.